Diagnosis and management of hypernatraemia in children - Zieg, Jakub (Acta paediatrica (Oslo), 2022)
Hypernatraemia is most commonly caused by excessive loss of solute-free water or decreased fluid intake; less often, the aetiology is salt intoxication. Especially infants, young children and individuals with a lack of access to water are at risk of developing hypernatraemia. Diagnosis is based on detailed history, physical examination and basic laboratory tests. Correction of hypernatraemia must be slow to prevent cerebral oedema and irreversible brain damage. This article reviews the aetiology, differential diagnosis and management of conditions associated with paediatric hypernatraemia. Distinguishing states with water deficiency from states with salt excess is important for proper management of hypernatraemic patients.
Keywords: diferenciální diagnóza; dítě; předškolní dítě; hypernatremie; kojenec; Diagnosis, Differential; hospitalizace; lidé; chlorid sodný; Infant; Humans; Hypernatremia; Child, Preschool; Hospitalization; Child; Sodium Chloride